Implementation of the Role of Correctional Guardians in the Development of Assisted Citizens in Correctional Institutions (Case Study at Class I Correctional Institutions in Surabaya) - Nur, Achmad Fauzi; Rizky, Muchammad Catur; Samuji, Samuji (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Crime cases that are still widely committed by the community have increased the volume of inmates in correctional institutions. According to the Police, most criminal incidents in Indonesia occurred at night, with 15,703 incidents, 15,501 criminal incidents during the day, and 15,501 crimes in the afternoon. Efforts to overcome social deviation include providing harsh sanctions, improving public relations, and facilitating reintegration to create a deterrent effect for perpetrators of social deviation. To overcome the increase in the number of inmates in correctional institutions, correctional guardians are needed to foster inmates to become better individuals when they return to society. This research method uses a descriptive qualitative approach in which direct observation, interviews, and questionnaires will be carried out. The results of this study stated that many yiang fostered the Class I Institution of Surabaya has provided programs to educate the inmates. However, the role of guardians carried out by guardians does not all go well; there are still obstacles and handling problems that are not immediately responded to, so the inmates feel inadequate in the services received.